Antidiabetic and antioxidant potential of Alnus nitida leaves in alloxan induced diabetic rats. (6th April 2020) - Sajid, Moniba; Khan, Muhammad Rashid; Ismail, Hammad; Latif, Sara; Rahim, Amna Abdul; Mehboob, Ramsha; Shah, Sayed Afzal
Abstract: Ethnopharmacological relevance: Leaves of Alnus nitida are used by local communities for the management of diabetes and in inflammatory disorders. Methods: Powder of shade dried leaves of A. nitida was extracted with methanol (ANME) and fractionated in escalating polarity i.e n-hexane (ANHE), chloroform (ANCE), ethyl acetate (ANEE) and soluble residual aqueous fraction (ANAE). The extract/fractions were evaluated for antidiabetic in vitro assays; α-amylase, α-glucosidase and dipeptidyl peptidase-4 (DPP-4). The in vivo investigations were carried out on ANEE and ANAE (100 mg/kg; 200 mg/kg, p.o.) in alloxan (125 mg/kg i.p.) induced hyperglycemic rats. Serum analysis was performed on liver, pancreas and kidney function markers. Analysis of antioxidant enzymes and genotoxic studies were carried out on pancreas, liver and kidneys tissues. GC-MS analysis was performed on ANME whereas HPLC analysis was carried out on ANME, ANEE and ANAE. Results: Preliminary in vitro assays indicated appreciable antidiabetic activity of ANEE and ANAE against α-amylase, α-glucosidase and DPP-4 assay. Furthermore, in vivo antidiabetic effect of ANEE and ANAE was inveterate by anti-hyperglycemic action in normal glucose loaded and diabetic glucose loaded animals. Single dose of alloxan (125 mg/kg) decreased the level of insulin and high density lipoprotein while raised the level of amylase and lipase, ALT, AST, total lipids, triglycerides, cholesterol, creatinine, BUN, CPK, CK-Mb in serum. Concentration of H2 O2, lipid peroxidation (TBARS) and nitrite was increased (P < 0.05) whereas level of tissue protein, glutathione content (GSH) and antioxidant enzymes decreased in pancreas, liver and kidneys as compared to control group. Administration of ANEE and ANAE for 14 days after induction of diabetes decreased the hyperglycemia and restored the level of these parameters. Histopathological and genotoxic studies also endorsed the defensive strategies of ANEE and ANAE. GC-MS analysis of ANME demonstrated the presence of antidiabetic constituents i.e. linalool, Vitamin E and phytol. Conclusion: Results obtained in this study suggests antidiabetic and antioxidant abilities and provides the scientific proof of the folklore medicine. Graphical abstract: Image 1